Effects of dietary restriction or swimming on lymphocytes and macrophages functionality from old rats. (February 2014) - Meneguello-Coutinho, Marcela; Caperuto, Erico; Bacurau, Aline Villa Nova; Chamusca, Grabriela; Uchida, Marco Carlos; Tibana, Ramires Alsamir; Pereira, Guilherme Borges; Navalta, James Wilfred; Wasinski, Frederick; Cavaglieri, Claudia Regina; Prestes, Jonato; Costa Rosa, Luis Fernando Bicudo Pereira; et al.
<x xml:space="preserve">Abstract</x> Although aging compromises the functionality of macrophages (MΦ) and lymphocytes (LY), and dietary restriction (DR) and exercise partially counterbalance immunosenescence, it is unknown what effects of both strategies have on the functionality of these immune cells. Rats were randomly distributed into adult control (AD), older group (OLD), older submitted to 50% of DR (DR) and older submitted to swimming (EX) (n = 10 in each group). The function of immune cells (proliferative index, phagocytic capacity and H2O2 production), the weight and protein content of lymphoid organs (thymus and spleen), plasma glutamine concentration, interleukins (IL-1, IL-2, IL-6) and, immunoglobulins (IgA and IgG) were analysed. There was an increase of 74% in body weight in aged animals as compared with the AD group, while body weight reduced 19% in the DR as compared with the OLD group. Swimming training stimulated MΦ phagocytosis, while the EX group presented a decrease of the proliferative capacity of LY from the mesenteric lymph nodes (44% and 62%, respectively), when stimulated with ConA and LPS as compared with the old rats. These data demonstrated that DR and exercise affects differentially MΦ and LY function.